Effect Of Quality Of Work Life And Work Stress On Employee Performance Through Organizational Commitments As Intervening Variables At The Branch Offices Of PT. Bank West Java And Banten. Tbk In Sumatera - Reza Hardian PRATAMA; Rr ERLINA; Habibullah JIMAD (International Journal of Environmental, Sustainability, and Social Science, 2021)
The decrease in performance in this study is caused by employee work stress which is influenced directly or indirectly. In the second and fourth hypotheses, we can see the influence of quality of work-life and work stress on employee performance through organizational commitment as an intervention. This research aims to find out what causes employee performance to decrease. Variable the case study is the employees of PT. Bank West Java and Banten Tbk in Sumatra branches covering Lampung, South Sumatra, Medan and Batam. This research uses quantitative research. This study uses primary data obtained by distributing questionnaires directly via google form at Bank Jawa Barat and Banten. The data obtained were then processed using the Smart PLS analysis tool. The population in this study were Bank Jawa Barat and Banten employees totaling 189 people. The sampling technique is a saturated sample or total sampling of 119 respondents. The results of this study are that quality of life has a significant positive effect on employee performance, work stress has a significant negative impact then, the quality of work-life through organizational commitment has a significant impact on employee performance, work stress has a significant negative effect on employee performance through organizational commitment as an intervention variable.